Effect of exogenous application of amino acids on fruit quality and productivity of peach (Prunus persica) - KAUR, MANJOT; SINGH, HARMINDER; JAWANDHA, S K (The Indian Journal of Agricultural Sciences, 2019)
The present investigations were carried out at Fruit Research Farm, Punjab Agricultural University, Ludhiana during 2016-17 to study the effect of exogenous application of amino acids (Peptone) on fruit quality, maturity and productivity of peach (Prunus persica L. Batsch) in sub-tropics of north India. The 6-year-old peach trees of cv. Florida Prince were sprayed with 0.25% and 0.50% of amino acid (Peptone P1 023), 7 and 14 days after full bloom and the sprays were repeated after 15 and 30 days. The highest yield (53.92 kg/tree) was recorded in T8 treatment (0.50% amino acid applied 14 days after full bloom and repeated after 15 days) while lowest in T12 treatment sprayed with triple spray of amino acids. All the double spray treatments of amino acids advanced fruit maturity by 4 days as compared to control. The mean maximum fruit weight (78.23 g) was recorded in T8 (0.50% amino acid applied 14 days after full bloom and repeated 15 days later) and minimum in the plants sprayed with triple sprays of amino acids (T12). The double spray treatments (T5 to T8) recorded lower fruit firmness indicating early maturity than control and other treatments. Maximum fruit TSS (12.10Â°Brix), highest total sugars content (5.12%) and lowest mean juice acidity (0.70%) was recorded in T8 treatment. Therefore, the double spray treatments of amino acids advanced fruit maturity, increased yield and improved fruit quality in peach.